PENERAPAN SISTEM BISNIS BERBASIS DIGITAL MARKETING DENGAN PENDEKATAN QUALITY FUNCTION DEVELOPMENT DALAM MENDUKUNG UMKM KOTA BATAM - Riki, Riki; Nopiana, Puspita Rama (JURSIMA, 2021)
It is especially based on various issues that are currently occurring in 2020. Indonesia's economy is currently experiencing a dramatic decline due to the Covid19 pandemic, which is particularly affecting the MSME in the city of Batam. During the Covid19 pandemic, most of the MSMEs in Batam are currently at risk of closing and closing their businesses due to the difficulty of earning income from their performance. Applying a digital marketing-based business system with a quality function development approach aims to build a digital marketing-based digital business system. The approach used in this study is a study using the Quality Function Development (QFD) approach. This approach is performed to get information based on customer feedback in the design of this system. Product identification and specification, concept development and selection, design and prototype analysis are performed after customer feedback is obtained. The results of our analysis of the application of this system are reliable in terms of information, convenience, ease of use, and transaction security. Functional criteria, on the other hand, include attractive looks, accurate transaction calculations, business actor relationships, security features, digital marketing to increase product presence, and the ability to upload photos in appropriate and informative resolutions.